An Analysis of Read-Ability of Learning Discourse in Indonesian Textbook Based on Curriculum 2013 - Kustina, Rika; Nasution, Wahidah; Simatupang, Yusrawati JR; Kasmi, Hendra; Mahmud, Teuku (Jurnal Ilmiah Teunuleh, 2023)
Textbooks or teaching materials are a source of information and knowledge for students. As the discourses contained in the textbooks should be well constructed, delivered with regard to the level of readability. This study aims to find out as well as describe the level of readability of learning discourse I in student textbooks. The results showed that of the 5 discourses analyzed, 4 of them did not have readability elements that were in accordance with the standards applied based on reygor charts. It is seen that the many incorrect use of words given for grade X. Moreover, (1 discourse) is appropriate or has the right element of readability given in the target grade. Thus, it can be concluded that the learning discourse I in the Indonesian textbook grade X is not appropriate given in the grade should be given to a grade that is one level above it.